Architectural Healing Spaces: How Design Protects, Rehabilitates Survivors of Abuse - Isola, Teegan (School of Architecture, Planning and Geomatics, 2024)
This dissertation delves into an exploration of the profound potential of architectural interventions in facilitating the healing process for survivors of abuse, with a particular focus on women and children. Acknowledging the significance of environments that promote user comfort, personal control, privacy, sensory engagement, and a connection to nature, the study recognises the pivotal role these factors play in psychological well-being, especially for victims of domestic violence. Motivated by a deep understanding of the impact of domestic violence and trauma, this dissertation is dedicated to the creation of healing spaces for women and children. Its primary objective is to investigate how architecture can actively support the mental healing process of individuals. The project centres on the idea that spatial interventions can act as catalysts for creating dignity, healing, and restoration for survivors of abuse. At the heart of this endeavour is the establishment of a sanctuary, designed to provide women with a safe, nurturing, and empowering environment to recover from past traumas and develop essential life skills, ultimately fostering personal growth and self-sufficiency. The sanctuary offers a range of spaces, including areas for counselling, workshops, communal activities, and private reflection, seamlessly harmonising with the natural surroundings. The project combines therapeutic healing practices with practical skills training, empowering women on their journey to recovery. This comprehensive training covers a diverse array of areas, from business and entrepreneurship to agricultural and computer skills, equipping women to take control of their own healing and future. Set against the backdrop of a women-run farm in the Sandveld region of the Western Cape, the design explores the juxtaposition between refuge and reveal, striving to strike a balance between safety and comfort, while fostering a profound connection with the natural world. Through the strategic layering of spaces, materials that signify both solidity and transparency, and a dedication to integrating the built environment with the natural landscape, the project exemplifies the potential of architecture to serve as a catalyst for healing, restoration, and transformation, offering nurturing not only to its inhabitants but also to the landscape.